Anita Desai’s Fire on The Mountain: An Ecofeminist Reading - Emara, Maha Abdel Moneim (Advances in Social Sciences Research Journal, 2017)
Ecofeminism, as a social, political and philosophic movement, considers the oppression of women and the exploitation of nature as interconnected phenomena. This paper analyzes Anita Desai’s Fire on The Mountain (1977) in the light of ecofeminist critical theories. The text explores how oppressive practices linked to patriarchal society operate forcefully on levels of gender and environment. It deploys a deft patterning of botanical, zoological, atmospheric and color imagery to convey the symbolic centrality of the narrative and the diverse analogies of the darker shades of nature and the darker aspects of femaleness.